2021
DOI: 10.1016/j.msard.2021.103042
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Australian bushfires and the COVID-19 pandemic on health behaviours in people with multiple sclerosis

Abstract: Background Crises and disasters disproportionally impact people with chronic health conditions such as multiple sclerosis (MS). Objective To assess the impact of the COVID-19 pandemic and the Australian Black Summer Bushfires on health behaviours in people with MS. Methods People with MS, carers, healthcare and advocacy professionals were recruited online between May-July 2020 for an online survey and telephone interviews. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…PwMS are less physically active than the general population, 6 and this may have been further reduced during the COVID-19 pandemic. 7,8 National and local restrictions aiming to slow down the spread of COVID-19 forced many venues offering physical activity to close, 7 reducing the availability of physiotherapy and exercise services and thus possibly decreasing the level and type of physical activity for PwMS. In the general population and in people living with disabilities there is emerging evidence that the COVID-19 pandemic has negatively affected physical activity behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PwMS are less physically active than the general population, 6 and this may have been further reduced during the COVID-19 pandemic. 7,8 National and local restrictions aiming to slow down the spread of COVID-19 forced many venues offering physical activity to close, 7 reducing the availability of physiotherapy and exercise services and thus possibly decreasing the level and type of physical activity for PwMS. In the general population and in people living with disabilities there is emerging evidence that the COVID-19 pandemic has negatively affected physical activity behavior.…”
mentioning
confidence: 99%
“…In the general population and in people living with disabilities there is emerging evidence that the COVID-19 pandemic has negatively affected physical activity behavior. [7][8][9][10][11] There is, however, a lack of knowledge regarding whether the COVID-19 pandemic has influenced physical activity in PwMS compared to prepandemic times.…”
mentioning
confidence: 99%
“…Indeed, 1 study estimated that almost half of the people with MS decreased their PAs during the COVID-19 pandemic [15]. Studies assessing the impact of COVID-19 restrictions on PA and exercise among people with MS use a cross-sectional research design and survey methodology, which do not delve into the unique perceptions and experiences of people with MS [15][16][17][18]. A deeper understanding of these issues can inform the development of programs that will more effectively address the unique needs of people with MS. To address this gap, this study used a qualitative research design and explored the impact of COVID-19 lockdown restrictions on exercise behavior among a small convenience sample of adults with MS enrolled in STEP for MS.…”
Section: Objectivementioning
confidence: 99%
“…But less research has investigated how cascading crises impact health behaviors . Marck et al ( 4 ) found that Australians diagnosed with multiple sclerosis experienced deterioration in a number of health behaviors during the summer bushfires in 2019–2020 and the COVID-19 pandemic, including reduced physical activity, increased alcohol consumption, and disrupted sleep patterns. Bell et al ( 5 ) linked existing health survey data with federal disaster declarations at the county-level data and found an association among older adults between exposure to a disaster and reduced physical activity but no association with smoking.…”
Section: Introductionmentioning
confidence: 99%